Impulse Buying in Shopee E-Commerce: The Role of Live Streaming, Flash Sales, and Customer Reviews among University Students in Semarang - Rahmeinda Kintia; Ali Maskur (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study aims to examine the effects of live streaming, flash sale, and customer review on impulse buying behavior of cosmetic products on the Shopee e-commerce platform among university students in Semarang City. This research employs a quantitative approach with a causal research design. Data were collected through questionnaires distributed to 96 respondents selected using a probability sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that live streaming has a positive and significant effect on impulse buying (t = 2.028; p < 0.05), indicating that real-time interaction and product visualization enhance consumers’ emotional engagement and stimulate spontaneous purchases. Flash sale has the strongest positive and significant effect (t = 3.640; p < 0.05), suggesting that time-limited promotions and perceived scarcity create urgency and encourage impulsive buying behavior. In contrast, customer review has a negative and insignificant effect (t = −0.279; p > 0.05), indicating that reviews tend to function as rational evaluation tools rather than emotional triggers. Simultaneously, all variables significantly influence impulse buying (F = 12.922; p < 0.05), with a coefficient of determination (R²) of 0.274. These findings suggest that impulse buying in e-commerce is primarily driven by emotional and promotional stimuli rather than informational factors. This study contributes to the understanding of consumer behavior in digital marketing contexts and provides practical implications for optimizing marketing strategies in e-commerce platforms.